2011
DOI: 10.1111/j.1479-828x.2011.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of medical students’ involvement in their obstetrics and gynaecology health care

Abstract: Patient perceptions of students' involvement in their obstetrics and gynaecology care are mainly positive. Satisfaction levels differ with the gender of the student, the age of the patient, the location of care and for those for whom English is their first language. Attention must be paid to informing patients of the presence and possible level of interaction of students in their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
30
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 19 publications
12
30
1
1
Order By: Relevance
“…This is fortunate, as our students only obtain limited experience with professional patients because of poor availability, even though experience with such patients appears to improve pelvic examination skills . This study also found a patient preference for female students being present in consultations and performing examinations, which correlates with other studies, and reiterates the extra challenge that male students face in obtaining such skills …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is fortunate, as our students only obtain limited experience with professional patients because of poor availability, even though experience with such patients appears to improve pelvic examination skills . This study also found a patient preference for female students being present in consultations and performing examinations, which correlates with other studies, and reiterates the extra challenge that male students face in obtaining such skills …”
Section: Discussionsupporting
confidence: 83%
“…One study found that 12.5 per cent of patients thought ‘prior awareness’ was an area requiring improvement in patient–student interaction in gynaecological consultations, which suggests that pre‐informing patients may increase patient acceptance . Westberg conducted a randomised double blind trial to investigate whether being given information about a gynaecology clinic prior to arrival would increase the patients' acceptance of medical students .…”
Section: Introductionmentioning
confidence: 99%
“…Others have also highlighted female patients being uncomfortable with male learners [7]. Patients may have individualized private matters which they would not want to share in front of a college student (e.g., sensitive parts of the history such as sexual concerns, or intimate parts of the physical exam).…”
Section: Discussionmentioning
confidence: 99%
“…Patients are having acute and shorter hospital stays and therefore finding quality clinical placements is becoming increasingly difficult [7]. An added pressure for many medical schools around the world are growing class sizes [8], a challenge that is not new, with the impact described as early as 1978 [9].…”
Section: Introductionmentioning
confidence: 99%